A reversed-phase HPLC method for determining tretinoin - Jiang Xin-guo; Xi Nian-zhu (Acta Pharmacologica Sinica, 2016)
Tretinoin (Tre) and its active stereo isomer isotretinoin (Iso) were simultaneously determined by reversed-phase high pressure liquid chromatographic method with a uv detector adjusted to 348 nm. Separation was accomplished on YWG-C18 column by using a MeOH:NH4Ac buffer (pH 6.0) 85:15 (vol:vol), chlorpromazine (Chl) being chosen as internal standard. Minimal detectable amount of Tre was 0.5 ng. Calibration curve was linear (r = 0.9999) in the concentration range of 25-2500 ng.ml-1. This method was used to determinate the transdermal amounts of Tre from three different preparations in Franz diffusion cell in vitro. The results showed that the proposed method could distinguish the transdermal differences from various formulations or different skin samples. In addition, it is able to be used in quantitative analysis of Tre and Iso.